(3fhGRd abgjIs - (3CHh YHO Gddg eMeO Hf GdeNJGQ Hf GdGYeT GdYdhj GdTfbjWj,J (B1107 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hMOg , agPg CLhHI GdTjN ZjQ eQJHI Ydi GdaUhd hGdCHhGH GdeJbOeI Hd Ydi GdCSFdI hGdfhGRd , QHeG jCJi HeSGFd eTJQcI ai Mce hjCJi HZjQgG , hQHeG jCJi , HGdSDGd hLhGHg cGedkG , hQHeG jCJi HGdLhGH Ohf eSCdg s
(3BNQgG (B:s
(3hSFd Yf OGQ HERGFgG QMHI de JPcQ Mjf jMda GdHGFY ChdkG Cfg eG bUO ONhdgG ai GdHjY EfJgJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ HYV cdeGJgG HGdMeQI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3Gdabg GdESdGejs